Peningkatan Knowledges dan Soft Skill Masyarakat dalam Produksi Sosis Jamur Sawit Berbasis Daging Ayam di Desa Rasau Jaya Kabupaten Kubu Raya Kalimantan Barat - Retno Budi Lestari; Andri Andri; Edy Permadi (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2026)
Rasau Jaya Village has extensive oil palm plantation areas that produce large amounts of unused empty fruit bunches, which support the growth of oil palm mushrooms. These mushrooms contain beneficial nutrients, including protein, dietary fiber, carbohydrates, and low-fat content, making them a potential alternative food ingredient. However, the community in Rasau Jaya Village faces challenges due to limited knowledge and soft skills in processing oil palm mushrooms into value-added products. Oil palm mushrooms have functional properties that allow them to be used as a filler ingredient in sausage production, particularly when combined with animal protein sources such as chicken meat. To address this issue, the Community Service Program (PKM) implemented counseling sessions on the benefits of oil palm mushrooms and hands-on training in producing broiler chicken–based oil palm mushroom sausages. The results showed a significant improvement in community capacity. Knowledge levels increased from 20% to 100% after counseling and socialization activities, while soft skills improved from 30% to 95% following direct practice in sausage production. In conclusion, counseling and practical training effectively enhanced community knowledge and soft skills, enabling residents to process oil palm mushrooms into nutritious products, including sausages, using oil palm mushrooms as a filler ingredient